Evaluation of antidiabetic and antibacterial activities of Horsfieldia macrothyrsa leaves extracts - Megawati, Megawati; Darmawan, Akhmad; Hudiyono, Sumi; Ariani, Novita; Primahana, Gian; Prastya, Muhammad Eka; Minarti, Minarti; Wulandari, Rika; Supriadi, Edi (Science, Engineering and Health Studies, 2025)
Cold maceration was used to extracting Horsfieldia macrothyrsa leaves with high lignan and alkaloid contents along with antidiabetic properties from methanol. This work examined the antidiabetic and antibacterial activities of methanol extract and other fractions from H. macrothyrsa leaves, utilizing α-glucosidase and antibacterial inhibition methods against some bacterial targets including Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Bacillus subtilis. This study found that the methanol extract (HMM) and ethyl acetate fraction of H. macrothyrsa (HME) leaves have antidiabetic potential, with IC50 values of 7.318 ± 0.57 and 6.694 ± 0.44 μg/mL, respectively. Interestingly, only the ethyl acetate (HME) fraction exhibited antibacterial activity against E. coli and S. aureus with MIC/MBC values at concentrations of 0.31/0.31 mg/L and 0.63/0.63 mg/L, respectively. As a result, the HME fraction was separated into 13 fractions using a gravity column chromatography method. The results revealed that the HME column chromatography fractions, namely F11 and F12, had the highest antidiabetic values. The best inhibitory power against all bacteria tested has been shown by F2 and F3, which have an inhibitory capacity of 8.67± 0.47 mm against S. aureus and 9.00 ± 0.00 mm B. subtilis bacteria on with MIC/MB values of 0.15/>0.15 mg/L. The HME fraction contained several bioactive compouds including the 7-hydroxy-3-methoxyflavone-2'-carboxylic acid and 8-acetyl harpagide, whereas the alkaloid group had 4-[(3R)-3-[Bis((2R)-2-hydroxy-2-phenylethyl)amino]]benzamide and 1,1–dimethylethyl 4-(4-aminobutyl)-1 piperidinecarboxylate, were also detected these compounds were tentatively identified using liquid chromatography-tandem mass spectrometry analysis (LC-MS/MS). These findings suggest that H. macrothyrsa leaves may have dual advantages as a reducing agent suggesting potential antidiabetic activity of avoiding diabetes (under 25 μg/mL) and against bacteria S. aureus and E. coli.